M139 Frailty And Premature Cardiovascular Ageing In Copd. (10th November 2014) - Albarrati, AM; Gale, NS; Enright, S; Munnery, M; Munnery, I; Saikia, S; Cockcroft, JR; Shale, DJ
Abstract : Background: Presence of comorbidities in chronic obstructive pulmonary disease (COPD) parallels the accumulation of multiple system deficits associated with ageing and assessed as frailty. An important association of frailty in the elderly is increased cardiovascular disease, which is also a major cause of mortality in COPD. 1 However, frailty has not been extensively studied in COPD. We hypothesised that frailty in COPD would be associated with biomarkers of greater systemic involvement including cardiovascular and indicating premature cardiovascular ageing. Methods: Frailty was determined as a Frailty Index (FI) using the 61-element comprehensive geriatric assessment questionnaire in 500 patients with stable COPD, confirmed with spirometry, and 150 non-COPD comparators. This cross-sectional study was taken from within the ARCADE study. Other assessments included body composition; handgrip strength (HGS); aortic pulse wave velocity (PWV); cardiac haemodynamics; 6 min walk distance (6MWD); Timed Up and Go (TUG) test; St George's Respiratory Questionnaire (SGRQ) and C-reactive protein (CRP). The FI was calculated by dividing the number of deficits that the patient had by the maximum, 61 Results: Patients and comparators were similar for age, BMI and gender proportion. The FI was greater in the COPD group; mean (95% CI), 0.15 (0.14–0.16) than in comparators, 0.05 (0.03–0.05), independent of age, p Conclusion: Patients with COPD were frail compared with the comparator group of current or ex-smokers, independent of age. Frailty status in the patients was associated with a greater severity of the extra-pulmonary involvement including cardiovascular risk based on greater aortic PWV. Increased aortic PWV in frail patients was independent of blood pressure. These findings are consistent with premature cardiovascular ageing in COPD. Reference: Newman et al . J Gerontol A Biol Sci Med Sci, 2001;56:M158-66